Clinical Cutaneous Features of Patients Infected With SARS-CoV-2 Hospitalized for Pneumonia: A Cross-sectional Study. (18th October 2020) - Mascitti, Hélène; Bonsang, Benjamin; Dinh, Aurélien; Assan, Florence; Perronne, Véronique; Leblanc, Thibault; Duran, Clara; Bouchand, Frédérique; Matt, Morgan; Le Gal, Aurélie; N'guyen Van Thanh, Julia; Lanore, Aymeric; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of a current pandemic worldwide. This virus can reach all organs and disturbs the immune system, leading to a cytokine storm in severe forms. We aimed to report cutaneous features among coronavirus disease 2019 (COVID-19) hospitalized patients. Methods: We performed a cross-sectional study on 1 given day among all patients hospitalized in acute care for COVID-19 and included all patients with cutaneous features. Follow-up 48 hours later was obtained. Results: Among 59 adult patients hospitalized on the day of the study in an infectious diseases ward for SARS-CoV-2 infection who were confirmed by molecular assay and/or radiological findings (computed tomography scan), 40 were included. Several cutaneous manifestations were found: macular exanthema (80%), face edema (32%), livedo (13%), urticarial rash (8%), purpura (5%), oral lichenoid lesions (33%), and conjunctivitis (18%). Cutaneous biopsy was performed in 17 patients. Histological findings showed mast cell hyperplasia (100%), superficial perivascular infiltrate of lymphocytes (94%), and superficial edema (47%) consistent with capillary leak. Conclusions: Various dermatological signs can be encountered during COVID-19. A macular rash was the most frequent. All cutaneous features could be related to a vascular leak process. Abstract : This cross-sectional study showed that cutaneous features are various among hospitalized patients with COVID-19. Macular rash was the most frequent and could be predictive of worsening. They seem related to an immune system disturbance, leading to a vascular leak process.